An immunoproteomics study of antisera from patients with gonorrhea identifies novel Neisseria gonorrhoeae proteins - Dijokaite-Guraliuc, Aiste; Humbert, Maria Victoria; Skipp, Paul; Cleary, David W.; Heckels, John E.; Christodoulides, Myron (Frontiers in Bacteriology, 2023)
Background Neisseria gonorrhoeae (gonococcus) is the causative agent of the sexually transmitted disease gonorrhea, for which no vaccines exist. Efforts are being made to identify potential vaccine protein antigens, and in this study, an immunoproteomics approach was used to identify protein signatures in gonococci that were recognized by sera from patients with gonorrhea. Methods Sera from patients with uncomplicated gonorrhea and from controls were reacted on Western blot with gonococcal whole-cell lysate separated by 2D electrophoresis. Reactive bands were excised and digested, and peptides were analyzed by mass spectrometry to identify protein hits. Proteins were analyzed with in-silico bioinformatics tools (PSORTb v3.0, CELLO, SOSUI-GramN, LipoP 1.0, SignalP 5.0, TMHMM 2.0, eggNOG-mapper 5.0) to select for surface-exposed/outer membrane proteins (OMPs) and exclude cytoplasmic proteins and most periplasmic proteins. Sera were tested for bactericidal activity against homologous and heterologous gonococcal strains. Results Patient sera reacted with 180 proteome bands, and 18 of these bands showed ≥2-fold increased reactivity compared with sera from individuals (n = 5) with no history of gonococcal infection. Mass spectrometry produced peptide signatures for 1,107 proteins, and after bioinformatics analyses, a final collection of 33 proteins was produced that contained 24 OMPs/extracellular proteins never previously studied to our knowledge, 6 proteins with homologs in Neisseria meningitidis that can generate functional immune responses, and 3 unknown proteins. The sera showed little or no significant bactericidal activity, which may be related to the immunoproteomic identification of contraindicated proteins Rmp and H.8 that can generate blocking antibodies. Conclusion Studies on the vaccine potential of these newly identified proteins deserve consideration.